Analisis Minat Beli E-commerce Bhinneka.com Studi Kasus Program Campus Marketplace di Kalangan Mahasiswa - Mohamad Febrianto; Zainal Abidin; Rastri Kusumaningrum (Peneliti.net, 2023)
Purchase intention is the tendency of consumers to buy a brand or take actions related to purchasing. E-commerce is the use of electronic technology to make sales / advertising using the internet. This Campus Marketplace program can be a space for learning and direct business practice for the campus academic community, so that students and campus academics who are pioneering or even just planning to start a small business are no longer confused in finding a 'market' as potential consumers of the goods or services they will provide. The results of the study answer that consumer buying interest in the Campus Marketplace Bhinneka.Com among students is a referential buying interest, namely a person's tendency to refer products to others and exploratory interest which describes the behavior of a person who is always looking for information about the product he is interested in and looking for information to support the positive characteristics of the product and the factors that influence consumer buying interest in the Campus Marketplace Bhinneka.Com among students due to personal factors, social factors, and situational factors.